2021
DOI: 10.1038/s41598-021-98605-5
|View full text |Cite
|
Sign up to set email alerts
|

Acetate rescues defective brain-adipose metabolic network in obese Wistar rats by modulation of peroxisome proliferator-activated receptor-γ

Abstract: We investigated the hypothesis that acetate ameliorates brain-adipose metabolic dysfunction (BAMED) in high fat diet (HFD)-induced obesity, possibly by modulation of peroxisome proliferator-activated receptor-γ (PPAR-γ). Ten-week-old male Wistar rats were randomly assigned into four groups (n = 6/group): Control, acetate and obese with or without acetate groups received vehicle (distilled water; po), acetate (200 mg/kg, po) and 40% HFD with or without acetate respectively. The treatments lasted for 12 weeks. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 75 publications
2
6
0
Order By: Relevance
“…The study identification, selection, and inclusion process are summarized in Figure 2 . After eliminating duplicates, in total, 139 articles were included in this review, 112 from the first search term containing obesity [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , ...…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study identification, selection, and inclusion process are summarized in Figure 2 . After eliminating duplicates, in total, 139 articles were included in this review, 112 from the first search term containing obesity [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , ...…”
Section: Methodsmentioning
confidence: 99%
“…Short-chain fatty acids consistently normalized or, in some cases, actually prevented HFD-induced alterations, such as weight gain [ 38 , 48 , 88 , 92 , 96 , 145 ], elevated insulin levels, and decreased leptin levels [ 48 , 92 , 96 , 146 ]. Consequently, SCFAs could be used in the future as a supplement to ameliorate weight gain.…”
Section: Short-chain Fatty Acids Between Diet and Metabolismmentioning
confidence: 99%
“…Blood glucose levels were monitored with a hand-held glucometer (ONETOUCH-LifeScan, Inc., Milpitas, CA, USA). Insulin sensitivity was determined using quantitative check for insulin sensitivity (QUICKI) as previously described [ 9 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Insulin resistance consequentially raises insulin level and prevents insulin suppression of fat lipolysis leading to peripheral lipid deposition, lipotoxicity and activated pro-oxidant/inflammatory pathways with non-adipose organs as key victims [ 7 ]. Existing evidence have shown ovarian TG accumulation and uric acid-mediated inflammation in connection with overweight in PCOS animal models [ 8 , 9 ]. Furthermore, IR-hyperinsulinemia could contribute to anovulation through stimulatory effects of luteinizing hormone (LH) on androgen production in the ovarian theca cells and via inhibition of sex hormone-binding globulin (SHBG) production by hepatocytes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A Previous research revealed that oral acetate ( 58 , 59 ), propionate ( 60 ), and butyrate supplementation ( 61 , 62 ) can improve the expression of lipid metabolism genes in mice with a HFD. Examples include the upregulation of cyclic adenosine monophosphate-responsive element binding protein-regulated transcription coactivator (CRTC) 2 and phosphorylated acetyl-CoA carboxylase (p-ACC), or downregulation of peroxisome proliferator-activated receptor (PPAR) γ, acetyl-CoA carboxylase (ACC), and sterol regulatory element binding protein 1 (SREBP1) ( 63 ).…”
Section: Points Of Contact Between Gut Microbiota and Cholesterol Met...mentioning
confidence: 99%